Extractive industries, revenue allocation and local politics - Francisco Javier Arellano-Yanguas; Andrés Mejia Acosta (United Nations Research Institute for Social Development (UNRISD), 2014)
The success of a developmental strategy based on the extraction of non-renewable resources is largely dependent on the share of revenues captured by the state from the extractive sector and the modalities that governments adopt to use and distribute those revenues. In the last two decades, local populations and subnational governments have demanded a greater decentralisation of extractive industry (EI) related revenues but the modalities and mechanisms adopted varied widely across cases. This paper looks at the existing criteria and reform modalities adopted to allocate and use EI revenues, and examines the political bargains that enabled such distribution. The paper focuses on four specific questions: a) How do central governments share (or distribute) the revenues from extractive industries with different levels of subnational government (vertical distribution)?; b) How do governments distribute EI revenues across extractive and nonextractive jurisdictions at subnational level (horizontal distribution)?; c) Which are the mechanisms and rules adopted by governments to allocate these resources?; and d) What is the bargaining potential of subnational territories to demand a more proportionate share of revenues? We identify two critical dimensions that have an impact on redistributive outcomes: the degree of bargaining power of subnational actors and the alignment between national and subnational political actors. We contend that local actors with strong bargaining power tend to obtain clearer and greater revenue sharing gains, but the political alignment between national and local elites will tend to produce, other things equal, a better redistribution of revenues across producing and non-producing regions. We posit that improved development outcomes may emerge in a context where revenue sharing agreements result from elite bargains that combine earmarked and flexible decision making mechanisms and benefit the whole of the population, however more research is needed. Finally, the paper identifies some knowledge gaps regarding the effectiveness of different decentralisation modalities to improve development outcomes at the local level.
Keywords: 330